Home alone: impacts of a Non-contributory Pension Program (BPC) on household composition - Tarsitano, Rodrigo Couto (2020)
This dissertation aims to identify a possible effect of Brazilian non-contributory pension (BPC) on elderly household composition. We explored the discontinuity of BPC pensioners density at age 65 generated by the minimum age eligibility criterion in a regression discontinuity design approach, using registry data on household composition (Cadastro Único). Thus, we investigate changes in household composition, as measured by a set of household characteristics as outcomes. Our results show an effect in the direction of smaller sizes of elderly's households, like a reduction in the family size and an increase in the propensity of living alone, among others. Aside from the cross-section variation in age eligibility, we construct panel information on household composition for the same elderly using longitudinal linkages that are possible in the registry date. The results are similar in this alternative strategy. This way, the higher propensity of living alone represents a higher low-income elderly financial independence. On the other side, the family size reduction indicates fewer spillover effects on younger relatives, diminishing BPC power as a poverty fight instrument.